Improved Methods for the Preparation of Fish Sausage from the Unwashed Mixed Minces of Low-Cost Marine Fish - Nowsad, AAKM; Hoque, MS; Hossain, MI; Shikha, MH (Progressive Agriculture, 2014)
Fish sausage was prepared from the unwashed minces of 5 low-cost marine fishes (LMF) viz., red jewfish (Johnius orgentatus), sea cat fish (Tachysurus thalassinus), jwelled shad (Ilisha filigera) horse mackeral (Megalaspis cordyla) and skipjack tuna (Sarda orientialis) of the Bay of Bengal. Six different blend compositions from 5 individual minces of LMF were prepared by blending 15 to 30% of the individuals minces. Sausage was prepared from such mince blends by improving the textural strength of the products through different cooking process, ingredients and spices. Textural quality was determined in terms of gel strength, cook loss, sensory softness/firmness (S/F) and chewiness/rubburiness (C/R). Proximate composition and gel forming ability of individual mince blend varied with compositional differences of individuals species. Among the six blends tested, blend C showed highest gel strength which constituted with higher proportion of mince from red jewfish, sea cat fish and horse mackerel. In mince blend C, composition of red jewfish, sea cat fish, horse mackerel, jeweled shad and skipjack tuna were 30%, 20%, 20%, 15% and 15%, respectively. Unwashed and washed individual minces and the mince blend C were incubated at different temperatures from 35° to 55°C and then cooked at 90° or 100°C. Among different heating regimes, unwashed mince blend C showed the highest gel strength at 50°C for 1 hr incubation. Further cooking of the incubated gel at 100°C optimally increased the gelling ability. Among the four cooking methods tested, (boiling, two-step heating, broiling and autoclaving) autoclave cooking at 115°C obtained best textured sausage with significantly increased breaking force, folding test score and chewiness/rubberiness values and decreased cook loss values. Sausages prepared at 115° and 120°C, however, showed almost identical textural quality. Texture and flavor of sausage was affected by washing of the mince but the sensory qualities were unaffected. DOI: http://dx.doi.org/10.3329/pa.v18i2.18192 Progress. Agric. 18(2): 157 - 166, 2007